Physiological Implications of Broiler Chickens Diet Fortified with Tiger Nuts (Cyperus esculentus) - Ilo, S.U.; Ugwu, O.A.; Ogba, C.U.; Ogbu , O.C. (International Journal of Poultry Science, 2020)
Background and Objective: The quest to ameliorate protein food shortages have continuously made researchers to seek alternative sources of feed stuff that will be cheaper and less competitive with man. Tiger-nut is the richest tuber in terms of protein. It is rich in vitamins and minerals. Using it in the diet of broiler birds in two growth phases (starter and finisher) promoted growth. This study was conducted to investigate the effect of tiger nut on the growth performance of broiler chicken. Materials and Methods: A total of eighty four broilers were used for the study. The birds were randomly assigned to four treatment groups with a total of 21 birds per treatment. The treatments were T1 (0%) T2 (5%) T3 (10%) and T4 (15%). T1 served as the control. The treatments were replicated 3 times with 7 broiler birds per replicate. Results: Weight gain was significantly (p